Defect-free poly(9,9-bis(2-ethylhexyl)fluorene-2,7-vinylene) for polymer light-emitting diode (PLED) devices - Piched Auragudom (2018)
The π-conjugated light-emitting polymer poly (9,9-bis(2-ethylhexyl) fluorene-2,7-vinylene) (PEHFV) was synthesized in defect-free form via Horner-Emmons coupling. The structure and properties of the polymer were characterized by1H NMR,13C NMR, UV-vis, photoluminescence (PL), and electroluminescence (EL) spectroscopies as well as gel permeation chromatography (GPC) and thermogravimetric analysis (TGA). The weight-average molecular weight (Mw) and polydispersity of the PEHFV were 34,000 g/mol and 2.3, respectively. The UV-vis spectra showed absorption maxima at 425 and 452 nm, and the PL emission spectra showed a maximum at 505 nm with a shoulder at 541 nm. The polymer was soluble in common organic solvents and easily spin-coated on indium-tin oxide (ITO)-coated glass substrates. A doublelayer light-emitting device with an ITO/PEDOT:PSS/PFV/ Al configuration was fabricated. The turn-on voltage for the PEHFV device was observed at 3.0 V.